Liturgy and Laity in Late-Antique Rome: Problems, Sources, and Social Dynamics - Mark Humphries (Studia Patristica, 2014)
That Christianity in late antiquity developed by means of interactions with local culturesand societies has long been understood, but hitherto scholars have only rarely investigatedthe extent to which such interactions influenced the evolution of the liturgy. Thisquestion is particularly urgent for our understanding of the early Roman liturgy becauserecent decades have witnessed a revolution in what is known about the development ofthe fabric and society of Rome between antiquity and the middle ages, largely as aresult of new archaeological investigations. This renders much earlier work on thesocial context of the early Roman liturgical developments outdated. The purpose of thispaper is to introduce liturgical scholars to the wealth of this new evidence from Rome,to outline how it has sparked a re-evaluation of Roman society between the fourth andseventh centuries, and to suggest ways in which this new knowledge can be brought tobear on efforts to trace the evolution of the early Roman liturgy.